(untitled) (Scientific journal of the Fergana State University, 2024)
In the first centuries AD, there was a large Kushan Empire in the southern regions of Central Asia, the Indian Peninsula, Afghanistan, southern Uzbekistan and southern Tajikistan, and the Parthian Empire in its western parts, Iran, Turkmenistan and the Black Sea region. , in them Hellenistic culture and "Hellenized culture" was created in the regions of Kang state, a union of large semi-peasant, semi-herding states in the north of these countries.